STUDI OPTIMASI PENENTUAN KADMIUM(II) SECARA VOLTAMMETRI STRIPPING ADSORPTIF - Deswati Deswati; Hamzar Suyani; Citra Buhatika (Jurnal Riset Kimia, 2010)
ABSTRACT Study of optimation cadmium(II) by adsorptive stripping voltammetry has been done. The aim of this study to get optimum conditions for determination of Cd(II). Parameters were done : potential accumulation, time accumulation, pH, supporting electrolite concentration and optimum of complex concentration. In this case, the optimum conditions were reached in potential accumulation -0.7 V, time accumulation 60 second, pH 7.0, NH4Cl 0.12 M, calcon concentration 0.12 mM. In the optimum condition was obtained with the relative standard deviation was 4.61% for eight replicates, measurements of 0.01 ppm. The method was applied to the direct determination of Cd(II) in water around Batang Air Dingin Lubuk Minturun and Muara Padang. Concentration Cd(II) in sample was equal to 7.359 μg/L and 3.659 μg/L with recovery of 99.04%. Keywords: cadmiun, adsorptive, stripping, voltammetry